2008
DOI: 10.1080/11263500802150225
|View full text |Cite
|
Sign up to set email alerts
|

JIP test for fast fluorescence transients as a rapid and sensitive technique in assessing the effectiveness of arbuscular mycorrhizal fungi inZea mays: Analysis of chlorophyllafluorescence

Abstract: We applied chlorophyll a fluorescence as a biomarker to assess the growth enhancement of maize plants after inoculation with the mycorrhizal fungi Piriformospora indica, Glomus mosseae, or a mixed culture (P. indica, G. mosseae and G. caledonium), and compared it with uninoculated plants (controls). The quantum efficiencies for pigment system II (j Po) were not much affected. The yield for electron flow (j Eo ¼ j Po * co) was highly responsive to P. indica and mixed culture. Electron transport per trapping cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 40 publications
0
19
2
2
Order By: Relevance
“…Moreover, the quenching analysis revealed an elevated fraction of 'open' PSII reaction centers in the mycorrhizal tomato plants despite of significant lower chlorophyll content in comparison to control plants (Table 2). In contrast, other authors reported unchanged maximum quantum yield of PSII photochemistry, but CO 2 uptake was not measured (Rai et al, 2008), or much lower F V /F M ratios (Fay et al, 1996;Paradi et al, 2003) than in the present study.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Moreover, the quenching analysis revealed an elevated fraction of 'open' PSII reaction centers in the mycorrhizal tomato plants despite of significant lower chlorophyll content in comparison to control plants (Table 2). In contrast, other authors reported unchanged maximum quantum yield of PSII photochemistry, but CO 2 uptake was not measured (Rai et al, 2008), or much lower F V /F M ratios (Fay et al, 1996;Paradi et al, 2003) than in the present study.…”
Section: Discussioncontrasting
confidence: 82%
“…PS II activity) has been hardly examined (Tsimilli-Michael et al, 2010;Paradi et al, 2003;Rai et al, 2008). We therefore performed a comprehensive analysis of many different photosynthetic parameters in parallel (Table 2, Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Results concerning these factors were however also contradictionary. Chlorophyll contents or chlorophyll fluorescence were enhanced (Tsimilli-Michael et al 2000;Estrada-Luna et al 2000;Sheng et al 2008 or showed no differences between mycorrhizal and non-mycorrhizal plants (Paradi et al 2003;Rai et al 2008). C assimilation is negatively influenced by high sugar concentrations in the leaves (von Caemmerer 2000).…”
Section: Photosynthesis In Mycorrhizal Plantsmentioning
confidence: 95%
“…translates shape changes of the OJIP transient to quantitative changes of a set of parameters van Heerden et al 2004;Rai et al 2008;Tsonev et al 2011). Photosynthetic activity was monitored by Chl fluorescence parameters provided by the JIP test ).…”
Section: Fluorescence Parametersmentioning
confidence: 97%